PASAMBAHAN KAMATIAN MASYARAKAT LUBUK TAROK: FORMULA DAN FUNGSI SOSIAL BAGI MASYARAKAT PENDUKUNGNYA - Septiani, Resty Maudina (Universitas Andalas, 2022)
This study aims to understand the narrative structure of Pasambahan Kamatian as one of oral literature of the people of Lubuk Tarok. This study is also intended to observe social functions of Pasambahan Kamatian for Lubuk Tarok community. Theory of formula by Albert B. Lord is used. Data were collected in the form of recording, transcribed and described, then analyzed. The result showed the formulas and formulaic expression of Pasambahan Kamatian which are syntactic formula and repetition formula. The formula inherited through two ways, observation and special informal education. The sosial function of Pasambahan Kamatian is the function to honor their dead realtives or loved ones, the function of dakwah, social interaction to avoid individualism, and education of social values.